Analysis of Shopee Adoption as a Medium for Tuition Payment at Universitas Mikroskil Using the UTAUT 3 Model - Saragih, Yuni Marlina; Ginting, Tri Wulandari; Elly (Ali Institute of Research and Publication, 2025)
The development of technology and information is progressing rapidly, encompassing all aspects of life. One aspect that has developed from technological and information advances is education, for example, digital tuition payments. At Universitas Mikroskil, tuition payments can be made using an electronic payment system, namely through the Blibli website/app. Since September 29, 2022, Universitas Mikroskil announced the addition of a tuition payment application, namely the Shopee application. This electronic tuition payment is expected to make it easier for students to fulfill their responsibilities. However, no test has ever been conducted regarding student acceptance of the Shopee application, specifically for tuition payments. Therefore, the purpose of this study is to test student acceptance of the Shopee application for tuition payments using the UTAUT 3 model. The test was conducted using the PLS-SEM statistical analysis method with a total of 186 respondents. The results show that the personal innovation variable in IT has a positive and significant effect on utilization intention, the habit variable has a positive and significant effect on utilization intention, and a positive and significant effect on usage intention. The utilization intention variable has a positive and significant effect on usage intention. The results of this study are expected to help Universitas Mikroskil in making decisions on selecting a better tuition payment application.